Developments in genetic engineering of novel acetogens - Mansfield, Robert Patrick William (2018)
The development of processes for sustainable energy and chemical production is of great importance for the health of our planet. Utilising suitable feedstocks such as renewable resources and existing waste streams is central to making such processes a reality. Microorganisms can be employed in the processing of a diverse range of such feedstocks, offering unique routes of production for useful and valuable chemical products. Acetogenic organisms, capable of fermenting single carbon (C1) feedstocks are especially interesting from the perspective of industrial application. Their natural metabolism and biochemistry enables fixation of low energy C1 compounds, under conditions which would typically be unfeasible with traditional chemical catalysts. Genetic research and development of new acetogenic species opens the door to industrially feasible, and economically attractive, sustainable bioprocessing.